Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—16. Pentacomia (Mesochila) procera (Chaudoir), P. (M.) conformis (Dejean), and P. (M.) proceroides sp. nov. (Coleoptera: Cicindelidae) - Moravec, Jiří (Zootaxa, 2016)
Results of the author’s revision of the type and other accessible specimens of the hitherto little known and partly confused species-complex of P. (M.) conformis (Dejean, 1831) and Pentacomia (Mesochila) procera (Chaudoir, 1860) are presented. Redescriptions of these externally similar species with lectotype designation of P. (M.) procera are provided, and a closely related species, P. (M.) proceroides sp. nov., is described as a new to science. The synonymy of Odontochila chaudoiri Dokhtouroff, 1887 with P. (M.) procera has been confirmed. Mesochila Rivalier, 1969, with type species Odontochila procera Chaudoir, 1860 (by original designation), is here provisionally maintained as a subgenus of Pentacomia Bates, 1872 (as originally and hitherto classified), although the present revision has disclosed diagnostic characters of a separate genus. The history of the taxonomy and distribution of these three very rare species, which are at present known only from the type specimens and several other, mostly historical specimens from Brazil, as well as illustrations in colour photographs of their habitus and diagnostic characters, are provided.